MINAT BELAJAR MAHASISWA TATA RIAS TERHADAP MATA KULIAH RIAS PENGANTIN SOLO BASAHAN DAN PAES AGENG YOGYAKARTA DI AKS-AKK YOGYAKARTA - Herina Yuwati; Tri Warsihapsari (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2022)
This study aims to determine how many students of the Cosmetology Study Program are interested in the Bridal Makeup Practice course at AKS – AKK Yogyakarta. This type of research includes descriptive research because the researcher seeks to describe and interpret the object according to what it is. In this study, the determination of research subjects was determined by sampling techniques. The panelists were 51 people—students of the Cosmetology Study Program in semesters IV and VI. Data was collected using interview, observation, and documentation techniques. Discussions and comments are used to obtain data about the students' learning interests in the Cosmetology Study Program towards the Bridal Makeup practice course. Documentation is used to describe the primary form of students' interest in the Bridal Makeup course when practicing the Bridal Makeup course. The data is analyzed with descriptive analysis techniques. The results showed that groups of students took the bridal makeup practice course because the provisions of the curriculum had to be taken. Some groups are interested in the Bridal Makeup course and already know the system's benefits and can be used as the primary job